Strangers in the car - Ewan, C. M., 1976- (Grand Central Publishing, 2025)
Abi and Ben are driving home down foggy country roads, arguing about having had to cut short their weekend away when they take a wrong turn. Abi is behind the wheel, but her eyes leave the road for a moment as she says something to Ben - just as he gasps. A man is in the road, waving a torch. Abi swerves to avoid him. Ben tells her they should stop and go back, but Abi refuses. It's dark, the roads are isolated and they don't know this stranger. But, as Abi continues on, they see a broken-down car. Every instinct is still telling Abi to drive by, but then she notices the woman holding a car seat with a baby in it. Abi can't bring herself to leave a mother and baby stranded in the middle of the night. But offering them a ride might take them down a dangerous road, a road from which they may never return...